Early selection for drought tolerance in popcorn based on gene effects estimated in seedlings - Carvalho, Carolina Macedo; Khan, Shahid; Teixeira do Amaral Junior, Antônio; de Lima, Valter Jário; de Souza Silva, José Gabriel; Catarino Fuly, Lara Moreira; Leite, Jhean Torres; Santos Junior, Divino Rosa dos; Viana, Flávia Nicácio; de Souza, Rosenilda; Vieira, Henrique Duarte; Kamphorst, Samuel Henrique (Frontiers in Plant Science, 2023)
Low rainfall rates are becoming increasingly frequent as a result of climate change, causing droughts and threatening world food security. Based on knowledge about the genetic basis of traits involved in stages of popcorn germination and seedling development under water stress, genotypes with potential for adaptation to adverse growing conditions can be early selected. To this end, data on genetic effects and combining ability of 10 popcorn parents were compiled, in order to propose breeding strategies for the development of cultivars better adapted to water stress in early stages. Forty-five diallel hybrids were evaluated under two different water regimes – water stress and full irrigation, respectively, corresponding to a water retention capacity of 25% and 70% of the germination paper. For seven days, the plants were daily watered as needed. Characteristics of the following groups were evaluated: germination traits (germination speed index and germination on the seventh day); shoot traits (length and dry weight); and root system (length, dry weight, root-to-shoot ratio, maximum root number, area of root network, specific and root network length, as well as root volume). Breeding for drought adaption in early stages of popcorn development can be successful when hybrids are used, due to the genetic effects of dominance (𝜙s), which control the traits evaluated in the seedling stage. The combinations L61 x P2 and L71 x P3 were recommended, in view of the better performance estimated for traits related to the shoot and root system.